2016
DOI: 10.1016/j.bmcl.2016.04.089
|View full text |Cite
|
Sign up to set email alerts
|

GroEL/ES inhibitors as potential antibiotics

Abstract: We recently reported results from a high-throughput screening effort that identified 235 inhibitors of the Escherichia coli GroEL/ES chaperonin system [Bioorg. Med. Chem. Lett.2014, 24, 786]. As the GroEL/ES chaperonin system is essential for growth under all conditions, we reasoned that targeting GroEL/ES with small molecule inhibitors could be a viable antibacterial strategy. Extending from our initial screen, we report here the antibacterial activities of 22 GroEL/ES inhibitors against a panel of Gram-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 50 publications
3
61
0
Order By: Relevance
“…Sequencing of Hsp65 genes within a family of mycobacteria can be used for sub-classification of mycobacterial species [3][4][5]. In bacterial species, Hsp65 is known as GroEL, and the human homologue is known as human Hsp60, with similar molecular functions in both bacterial and human cells [6,7]. Previous studies demonstrated the presence of anti-Hsp65 antibodies within the circulation of patients with a variety of chronic conditions, including autoimmune diseases such as multiple sclerosis (MS), systemic lupus erythematosus (SLE), and Crohn's disease (CD), as well as other chronic conditions such as heart disease, atherosclerosis, and different types of cancers [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing of Hsp65 genes within a family of mycobacteria can be used for sub-classification of mycobacterial species [3][4][5]. In bacterial species, Hsp65 is known as GroEL, and the human homologue is known as human Hsp60, with similar molecular functions in both bacterial and human cells [6,7]. Previous studies demonstrated the presence of anti-Hsp65 antibodies within the circulation of patients with a variety of chronic conditions, including autoimmune diseases such as multiple sclerosis (MS), systemic lupus erythematosus (SLE), and Crohn's disease (CD), as well as other chronic conditions such as heart disease, atherosclerosis, and different types of cancers [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…33 We have since found that several of our chaperonin inhibitors exhibit antibiotic effects against Gram-positive and Gram-negative bacteria. 35 One of the most potent GroEL/ES inhibitors that we discovered was compound 1 (Figure 3), which inhibited both the substrate refolding and ATPase functions of the chaperonin system. 33,35 Unfortunately, compound 1 was inactive against the panel of bacteria we tested against, suggesting it may not be a good candidate for antibacterial development.…”
mentioning
confidence: 99%
“…35 One of the most potent GroEL/ES inhibitors that we discovered was compound 1 (Figure 3), which inhibited both the substrate refolding and ATPase functions of the chaperonin system. 33,35 Unfortunately, compound 1 was inactive against the panel of bacteria we tested against, suggesting it may not be a good candidate for antibacterial development. 35 However, we found a related analog in the PubChem database where the benzimidazole core is replaced by a benzoxazole (Figure 3, compound 2e-p, PubChem CID #1098316).…”
mentioning
confidence: 99%
See 2 more Smart Citations